Islams and modernities - ʻAẓmah, ʻAzīz (Verso, 2009)
Challenging the similarly romantic, a historic and irreconcilable notions of Islamic and Western cultures, this book cuts through conventional wisdom and common cliches to highlight the plurality and historicity of both. For Aziz Al-Azmeh, the Orientalist and racist view of Islam is nothing but the mirror-image of the myths propagated by the Islamic fundamentalists and radicals. In this book he demonstrates both views share an erroneous and an historical conception of Islam as an unchanging and monolithic entity. Moreover, this analysis dissects the mutual implication of both the dominant Western discourse and its supposed primary opponent, postmodernism, in this form of essentialism. There is no one, homogeneous Islam, and this book highlights the diversity and plurality of forms of the Muslim tradition, seeking to understand historically the phenomenon of fundamentalism, amongst other strands, as a profoundly modern ideology. Challenging the stereotypes and legends of both its opponents and proponents, the book traces how political Islam breaks with core elements of the Muslim tradition and, at the same time, roots many of its concepts in European reactionary and romantic thought.